2016
DOI: 10.1016/j.cct.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Prepare, a randomized trial to promote and evaluate weight loss among overweight and obese women planning pregnancy: Study design and rationale

Abstract: Background Women who are overweight or have obesity at pregnancy onset, and those who gain excessive weight during pregnancy, are at increased risk of pregnancy-related complications and large for gestational age infants. Objective This report describes methodology for the Prepare study, a randomized, controlled clinical trial testing a preconception and pregnancy weight management program for women who are overweight or have obesity (BMI ≥ 27 kg/m2). Outcomes This trial examines multiple pregnancy and neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 59 publications
(67 reference statements)
0
20
0
Order By: Relevance
“…We recruited participants from Kaiser Permanente Northwest (KPNW), a nonprofit integrated healthcare system serving individuals in Oregon and Southwest Washington. The study was conducted and reported in accordance with a previously published protocol 6 that was approved by the KPNW institutional review board. A Data and Safety Monitoring Board provided independent study monitoring.…”
Section: Study Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…We recruited participants from Kaiser Permanente Northwest (KPNW), a nonprofit integrated healthcare system serving individuals in Oregon and Southwest Washington. The study was conducted and reported in accordance with a previously published protocol 6 that was approved by the KPNW institutional review board. A Data and Safety Monitoring Board provided independent study monitoring.…”
Section: Study Settingmentioning
confidence: 99%
“…5 We conducted a pragmatic randomized clinical trial to test the efficacy of a behavioral weight management intervention initiated before pregnancy for women who were overweight or obese and were planning pregnancy. 6 The intervention consisted of individualized health coaching phone sessions. We hypothesized that women assigned to the intervention would lose more weight before pregnancy and gain less weight during pregnancy than women assigned to a usual care control arm, resulting in a lower likelihood of exceeding National Academy of Medicine (NAM) guidelines for GWG, 4,7 lower infant birthweight, and better perinatal outcomes.…”
mentioning
confidence: 99%
“…A couple of trials are currently recruiting in this area. 34,35 Hopefully these on-going trials will be able to provide some answers on what type of programs can help women of reproductive age to lose weight, and whether these programs can lead to better obstetric outcomes, and healthier metabolic status for women and their offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Two Cochrane reviews investigating the effectiveness of preconception and antenatal health programs and interventions to improve pregnancy outcomes or reduce weight in obese women, identified no eligible studies [10,11]. A more recent scoping review of randomised controlled trials of behavioural interventions supporting women of childbearing age in the prevention and treatment of overweight and obesity, only identified one intervention in the preconception period, the Prepare study protocol [12], which has gestational weight gain as the primary outcome.…”
Section: Work Package 1: Defining and Understanding The Population Through Routine Datamentioning
confidence: 99%